Design and analysis on small scale fixed-pitch Straight Bladed Vertical Axis Wind Turbine (SB-VAWTs) - Ji, Xiao Na (2013)
For the past few decades, researchers working on straight bladed vertical axis wind turbine (SB-VAWT) have faces many challenges in its analysis, modeling and design. This result in the development of the SB-VAWT being very slow which gave rise to the misconception that the SB-VAWTs is inherently inefficient. In this regards, overall performance study on SB-VAWT is necessary. The scope of present research work consists of three main areas, namely: experimental, computational and analytical studies.